Blue Laser Triggered Hemostatic Peptide Hydrogel for Gastrointestinal Bleeding Treatment - Luo, Qiang (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.